Review on the phytochemistry and toxicological profiles of Aloe vera and Aloe ferox - Nalimu, Florence; Oloro, Joseph; Kahwa, Ivan; Ogwang, Patrick Engeu (Future Journal of Pharmaceutical Sciences, 2021)
Background: Aloe vera and Aloe ferox have over the years been among the most sought-after Aloe species in the treatment of ailments worldwide. This review provides categorized literature on the phytochemical and scientifically proven toxicological profiles of A. vera and A. ferox to facilitate their exploitation in therapy. Main body of the abstract: Original full-text research articles were searched in PubMed, ScienceDirect, Research gate, Google Scholar, and Wiley Online Library using specific phrases. Phenolic acids, flavonoids, tannins, and anthraquinones were the main phytochemical classes present in all the two Aloe species. Most of the phytochemical investigations and toxicity studies have been done on the leaves. Aloe vera and Aloe ferox contain unique phytoconstituents including anthraquinones, flavonoids, tannins, sterols, alkaloids, and volatile oils. Aloe vera hydroalcoholic leaf extract showed a toxic effect on Kabir chicks at the highest doses. The methanolic, aqueous, and supercritical carbon dioxide extracts of A. vera leaf gel were associated with no toxic effects. The aqueous leaf extract of A. ferox is well tolerated for short-term management of ailments but long-term administration may be associated with organ toxicity. Long-term administration of the preparations from A. vera leaves and roots was associated with toxic effects. Short conclusion: This review provides beneficial information about the phytochemistry and toxicity of A. vera and A. ferox and their potential in the treatment of COVID-19 which up to date has no definite cure. Clinical trials need to be carried out to clearly understand the toxic effects of these species.
Keywords: Aloe vera; Aloe ferox; Aloe; Phytochemistry; Toxicity; Review; Safety